Physiological characteristics of two accessions of moringa (Moringa oleifera Lam.) at different planting sites in Madura - Catur Wasonowati; Endang Sulistyaningsih; Didik Indradewa; Budiastuti Kurniasih (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
Moringa plants grow in Sumenep with semi-intensive planting at the moor and several planting sites. Sumenep is one of the districts in Madura Island, which is categorized as a dry area based on the Oldeman climate classification. Based on the color of the leaf stalk, moringa plants growing in Sumenep area are categorized as green and purple moringa. The study aimed to examine the differences in physiological characteristics of two accession of moringa plants at different planting sites in Madura. The study was arranged in Oversite Sub-sampling Design with planting site as first factor consisting of Bluto with E5 climate type and Guluk-guluk with D3 climate type. Meanwhile, the second factor was the type of moringa consisting of moringa with green and purple leaf stalks. The results showed that the different planting sites represented the differences in environmental elements, which influenced the physiological characteristics of moringa plants. Based on the observation in September 2016, moringa plants with green stalks planted in Guluk-guluk had high ANR content. The stomatal opening on moringa leaves with green stalks was larger than that on moringa plants with purple stalks, whereas ANR content in green-stalked moringa was lower than in the purple-stalked ones. Meanwhile, in February 2017, the purple-stalked moringa plants planted at Bluto had the highest transpiration rate and proline content compared to the others.